Pierre Vidal-Naquet. El mundo de Homero. Trad. Daniel Zadunaishy. Buenos Aires, Fondo de Cultura Económica, 2001. 124 pp. - Guevara de Álvarez, María Estela (2003)
Fil: Guevara de Álvarez, María Estela. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras